A Sustainable Approach to the Stereoselective Synthesis of Diazaheptacyclic Cage Systems Based on a Multicomponent Strategy in an Ionic Liquid - Kumar, Raju Suresh; I. Almansour, Abdulrahman; Arumugam, Natarajan; Altaf, Mohammad; Carlos Menéndez, José; Kumar, Raju Ranjith; Osman, Hasnah (MDPI, 2016)
The microwave-assisted three-component reactions of 3,5-bis(E)-arylmethylidene] tetrahydro-4(1H)-pyridinones, acenaphthenequinone and cyclic -amino acids in an ionic liquid, 1-butyl-3-methylimidazolium bromide, occurred through a domino sequence affording structurally intriguing diazaheptacyclic cage-like compounds in excellent yields.